The effect of simulating body fluid on the structural properties of hydroxyapatite synthesized in the presence of citric acid - Kaygili, Omer; Keser, Serhat; Kom, Mustafa; Bulut, Niyazi; Dorozhkin, Sergey V. (Springer Heidelberg, 2016)
In present work, the effect of citric acid (CA) addition in different amounts (0, 1, 5 and 10 ml) on the structure of hydroxyapatite (HAp) was investigated using X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM) and energy dispersive X-ray (EDX) spectroscopy techniques. The crystallite dimensions, lattice parameters, unit cell volume, crystallinity percentage and Ca/P molar ratio were found to be affected by the CA content. To investigate the influence of CA on the bioactive properties of the HAp samples and to determine the optimum amount of CA, in vitro soaking tests in simulated body fluid (SBF) were performed. Although the samples' morphology was found to be affected by neither the amount of CA nor the soaking time in SBF, the soaking results revealed that the maximum changes in the Ca/P ratio were found for the HAp samples prepared in the presence of the highest amounts of CA, which pointed out to the highest bioactivity of these samples.
Keywords: Hydroxyapatite; Citric acid; Bioceramics; Simulated body fluid